ANALYSIS ON THE IMPACT WORK FROM HOME (WFH) ON THE TEACHING ENGLISH DURING THE COVID-19 PANDEMIC IN MADRASAH ALIYAH NEGERI TOLITOLI - Inda Indrawati; Siti Rahma Khaisya (Jurnal Inovasi Penelitian, 2021)
The purpose of this research was to determine the positive and negative impacts of working from home (WFH) in teaching English during the COVID-19 pandemic at Madrasah Aliyah Negeri Tolitoli. This type of research is a qualitative research whose data sources consist of three English teachers, namely SLM, IDR and WHB. Methods of data collection using interviews. The results of this study indicate that working from home has positive and negative impacts. (1) Positive Impact. (a) Teachers can learn some new applications. (b) Students are easier to learn again by using Handphones. (2) Negative impact. (a) Teachers find it more difficult to transfer their knowledge to students while working from home. (b) Students cannot participate in learning activities because some students do not have pulse data and are in places that do not have a network, while learning is done online. (c) Teachers cannot conduct moral assessments to students because they do not meet face to face.